Nutrition research methodologies - Lovegrove, Julie; Sharma, Sangita; Hodson, Leanne; Lanham-New, Susan A. (Wiley-Blackewell, 2015)
A new book in the acclaimed Nutrition Society Textbook Series, Nutrition Research Methodologies addresses the rapidly advancing field of nutrition research. It covers the diverse methodologies required for robust nutritional research to ensure thorough understanding of key concepts, both for students at undergraduate and postgraduate levels and for scientists working in nutrition research.Combining theory with practical application, Nutrition Research Methodologies addresses both traditional research methods and new technologies, and focuses on a range of complex topics, including energy comp